KAJIAN KENDALA DAN PEMECAHAN MASALAH PEMBELAJARAN AFEKTIFDALAM PENDIDlKAN AGAMA ISLAMPADASEKOLAH MENENGAH ATAS DI KOTA YOGYAKARTA - Maksudin Maksudin (LPMPP Universitas Negeri Yogyakarta, 2005)
This article is about adescriptive-qualitative research made to identify and describe the constraints of affective learning in the religious education affiliated to Islam at senior high schools in the city ofYogyakarta and the alternative strategies ofproblem:solving used by teachers of the religion in overcoming the constraints. The research data were collected from the whole population of such teachers at both state and private senior high schools all over the city by using questionnaires and interview guidelines.The research findings indicate that, in conducting affective teaching, those teachers are faced with numerous constraints related to their students' self-esteem, interest, motivation, attitude, value system, and faith. The constraints may be internal or external in origin, that is, caused by factors coming from the students themselves or by those coming from elsewhere. The teachers' efforts to overcome the constraints may also be internal in type, made to solve problems caused by factors of the first type above, or external in type, made to solvt: problems caused by factors of the second type above which have a share in causing the constraints external in origin. In addition, the findings also indicate that, in general, the teachers still lack fullunderstanding of and are not yet fully aware of the model of affective